DCell: A Scalable and Fault-Tolerant Network Structure for Data Centers - Guo, Chuanxiong; Wu, Haitao; Tan, Kun; Shi, Lei; Zhang, Yongguang; Lu, Songwu (SIGCOMM08, 2008)
A fundamental challenge in data center networking is how to efficiently interconnect an exponentially increasing number of servers. This paper presents DCell, a novel network structure that has many desirable features for data center networking. DCell is a ecursively defined structure, in which a high-level DCell is onstructed from many low-level DCells and DCells at the same level are fully connected with one another. DCell scales doubly exponentially as the node degree increases. DCell is fault tolerant since it does not have single point of failure and its distributed fault-tolerant routing protocol performs near shortest-path routing even in the presence of severe link or node failures. DCell also provides higher network capacity than the traditional tree-based structure for various types of services. Furthermore, DCell can be incrementally expanded and a partial DCell provides the same appealing features. Results from theoretical analysis, simulations, and experiments show that DCell is a viable interconnection structure for data centers.